2022
DOI: 10.1515/med-2021-0406
|View full text |Cite|
|
Sign up to set email alerts
|

lncRNA ACTA2-AS1 inhibits malignant phenotypes of gastric cancer cells

Abstract: Gastric cancer (GC) is one of the most common malignancies in digestive system. Accumulating evidence reveals the critical role of long noncoding RNAs (lncRNAs) in GC development. The study aimed to explore the functions and mechanism of lncRNA actin alpha 2, smooth muscle antisense RNA 1 (ACTA2-AS1) in GC. Reverse transcription-quantitative polymerase chain reaction analyses and subcellular fractionation assays showed that ACTA2-AS1 was lowly expressed in GC cells and was mainly distributed in the cytoplasm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
(68 reference statements)
0
3
0
Order By: Relevance
“… Li et al (2022) found that KCNQ1OT1/miR-556-3p/CLIC1 axis may promote GC growth and metastasis. Liu et al (2022) found that ACTA2-AS1 (lncRNA) suppressed the malignant phenotype of GC cells by targeting the miR-378a-3p/PLCXD2 axis as ceRNA. Liu et al (2022) revealed the potential molecular mechanism of RBMS1 to promote GC metastasis, suggesting that RBMS1 may be a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“… Li et al (2022) found that KCNQ1OT1/miR-556-3p/CLIC1 axis may promote GC growth and metastasis. Liu et al (2022) found that ACTA2-AS1 (lncRNA) suppressed the malignant phenotype of GC cells by targeting the miR-378a-3p/PLCXD2 axis as ceRNA. Liu et al (2022) revealed the potential molecular mechanism of RBMS1 to promote GC metastasis, suggesting that RBMS1 may be a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…They protect the body from tumor invasion, block tumor growth, and promote the normal development of cells ( Kontomanolis et al, 2020 ). LncRNA actin alpha 2, smooth muscle antisense RNA 1 (ACTA2-AS1) can suppress malignant phenotypes of GC cells as it can function as a ceRNA to bind to miR-378a-3p and antagonize the inhibitory impacts of miR-378a-3p on the expression of phosphatidylinositol-specific phospholipase C X domain containing 2 (PLCXD2) ( Liu et al, 2022 ). PLCXD2 is linked to an enhanced risk of esophageal squamous cell carcinoma in the Han Chinese population ( Wang et al, 2019c ).…”
Section: Lncrnas Regulate Emt-induced Metastasis In Gc Through Spongi...mentioning
confidence: 99%
“…A previous study identified a series of differently expressed ncRNAs in breast cancer from the Cancer Genome Atlas, including 55 lncRNAs, 88 miRNAs, and 1465 mRNAs, where lncRNA ACTA2-AS1 (lncRNA actin alpha 2, smooth muscle antisense RNA1) was found to be downregulated [ 7 ]. The function of ACTA2-AS1 has been illustrated in prior studies, such as colon adenocarcinoma, lung adenocarcinoma, and gastric cancer, with abnormal expression [ 8 10 ]. The upregulation of miR-532-5p in TNBC was leaked out in a previous expression profile of miRNAs in breast cancer at different onset stages [ 11 ], and its enhanced effect was also revealed in the cellular processes of breast cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%